Decreasing costs of renewables: Analysis of energy sector planning and climate policy in Indonesia - Jose Antonio Ordonez; Johannes Eckstein (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
This study analyses the processes and assumptions underlying the development of Indonesia's NDC and its revision in 2020. The assumptions underlying the related energy sector documents (KEN, RUEN, RUKN, RUPTL) and their relationships are also assessed. The study is completed by giving a snapshot of the current state of discussion around constraints related to renewable energy. The unconditional target of Indonesia's NDC foresees a reduction of GHG emissions of 29% relative to a Business-as-Usual (BAU) scenario (41% conditional to international support). It specifies that electricity generation shall reduce emissions by 18.8% relative to BAU. The overall target of a 29% and 41% have been set by a non-public process. The sectoral shares of GHG reductions are determined by the responsible ministries (ESDM in case of the energy sector), with modelling performed by academic institutions (e.g. BTI for energy). This modelling is partly based on existing plans of the energy sector. Data underlying this modelling is not public, but underlying socio-economic assumptions suggest that the BAU scenario overestimates emissions. The NDC has no influence on planning in the energy sector but should be considered a by-product of existing planning documents. The process underlying the current revision is repeated for the current revision of the NDC and likely also for creation of the LTS. The ambition under the revised NDC will not be increased. The share of renewable energy in the NDC follows from a cascade of energy planning documents (KEN, RUEN, RUKN, RUPTL), which pass the target from the most overarching energy plans to the NDC. Arguably the most important target related to renewable energy planning in Indonesia set down by the countries' energy strategy KEN, to reach 23% renewable energy in each sector in total primary energy supply in 2025. The assumptions underlying this target are not known and can therefore not be contested. The national energy plan RUEN makes this target more specific in terms of technology. The power sector plan by the ministry of energy RUKN and the power sector plan by the utility RUPTL all consider 23% renewable energy target. Besides that, these plans remain largely disconnected from each other. [...]
urn:nbn:de:0011-n-6156250
Keywords: 330